HIV/AIDS KNOWLEDGE AND SEX RELATED HEALTH SEEKING ATTITUDE AMONG YOUNG ADULTS IN KARACHI, PAKISTAN - Alia Nasir; Saima Merchant; Badil (ziauddin University, 2024)
Background: The epidemic of acquired immunodeficiency syndrome (AIDS) is considered as a big health problem. Therefore, in the absence of knowledge seeking behavior, issues cannot be handled adequately. Thus, the study is aimed to assess the knowledge about human immunodeficiency virus (HIV/AIDS) and sex-related health seeking attitude among young adults attending family-practice clinics in Karachi, Pakistan. Methods: Across-sectional study was accomplished in family medicine clinics affiliated with a tertiary care private sector teaching hospital in Karachi. Both Male and female gender, 586 subjects were approached by convenient non-probability sampling method. Participants who came to visit family medicine clinics for any reason with age between 18 to 24 years and never married were enrolled for the study. Structured and pretested tool was used to gather the data. Along with socio-economic variables, inquired the level of knowledge about the transmission, cure and prevention of HIV/AIDS. Furthermore, study participants were also asked about the health and education-seeking attitude regarding sexual problems. Results: Among 586 participants, males were 335 (57.2%) and females 251 (42.8%). Majority of them had knowledge that HIV can be transmitted by blood/blood products (92.7%), un-sterilized needles/syringes (85.3%) and unsafe-sex (93.5%). However, misconceptions were also present such as transmission of HIV by mosquito-bite, public toilets/swimming pools and food/water. Furthermore, 82.9% of study subjects believed that HIV is a vaccine preventable disease and 78.5% stated that AIDS is curable. Over 50% felt that their level of knowledge about HIV/AIDS is insufficient, and 72.7% subjects preferred school as a better source for providing sexual-health education, and the difference of these responses by sex were not significant. However, only 17.9% females preferred electronic media for providing sexual-health education compared to 30.7% males (p<0.01) and 51.4% females stated allopathic doctors as better choice to consult for sexual problems compared to 36.1% males (p<0.01). Conclusion: The study concluded that the majority of young adults have inadequate knowledge and misconception about HIV/AIDS